Change in physiological parameters of calves of various breeds under the transport and pre-slaughter stress - VLADIMIR IVANOVICH LEVAKHIN; IVAN FIODOROVICH GORLOV; ELEMES AZHMULDINOVICH AZHMULDINOV; YURIY IVANOVICH LEVAKHIN; GALIMZHAN KALIKHANOVICH DUSKAEV; ELENA YURIEVNA ZLOBINA; EKATERINA VLADIMIROVNA KARPENKO (Smujo International, 2017)
Levakhin VI, Gorlov IF, Azhmuldinov EA, Levakhin YI, Duskaev GK, Zlobina EY, Karpenko EV. 2017. Change in physiological parameters of calves of various breeds under the transport and pre-slaughter stress. Nusantara Bioscience 9: 1-5. The purpose of the research was to study the effect of the animal breed on the stress resistance of young cattle during the motor transportation. Six groups of animals were chosen for the experiment. The first group consisted of calves crossbred from dairy Black and White cows with Hereford bulls, the second – of calves crossbred from dairy cows of Bestuscheff breed with Hereford bulls, the third – of calves purebred of Simmental, the fourth – of calves purebred of Hereford, the fifth – of calves purebred of Aberdeen-Angus, and the sixth – of calves purebred of Limousine breed. The total length of transport was 180 km of highways and local roads. The route consisted of a 5-hour trip without a rest period. The greatest loss in the body weight was determined in the Limousine calves. The calves purebred of Hereford and Simmental breeds are more stress-resistant during the transporting and the pre-slaughter treatment.